The Crucial Role of the Eyes in Predicting Facial Attractiveness from Parts - Xiaolan Gao; Hongjie Li; Xiao Han; Yong Ren; Yue Qi; Wenfeng Chen (Behavioral Sciences, 2025)
Perceiving facial attractiveness based on partial information is a common experience in social interactions, where we often view only parts of faces. However, our understanding of predictions of the whole face from its parts remains limited. This study investigated this by dividing faces into the top and bottom halves (Study 1) and the forehead, eyes, nose, and mouth (Study 2). We compared how attractiveness was predicted from these parts versus when the whole face was fully observed. In the findings, overestimations occurred when predicting from the eyes (or the top half). Similarly, predictions from the nose resulted in overestimations, though to a lesser extent. In contrast, no difference was found between the predicted and observed attractiveness of the whole face when predicting from the mouth (or the bottom half). Further analysis revealed that the eyes were the most significant predictor of facial attractiveness across all facial features. Interestingly, higher attractiveness of the eyes was associated with a greater extent of overestimations in predictions from the eyes, whereas predictions from other parts exhibited a reduced extent of overestimations. These findings implied that predictions were influenced by the eyes, underscoring the critical role the eyes play in the process of predicting facial attractiveness.